BREAK EVEN POINT ANALYSIS OF BUDGETING SYSTEM UD. BAROKAH TANI IN KABUPATEN BREBES - Purwanto, Medi Tri (PERMANA, 2012)
The purpose of this study is (1) To determine whether the total sales value at UD. Barokah Tani in Kabupaten Brebes is located at the level of the break even point . (2) To determine whether the percentage decline in the value of total sales of the company can be tolerated so as not to experience losses (margin of safety) and are under contribution ratio . (3) To determine whether the change in the value of total sales has a positive effect on corporate earnings changes The research method used is a case study at UD. Barokah Taniin Kabupaten Brebes, while the formula used to test the hypothesis Break Even Point, Margin Of Safety, Contribution Margin Ratio, Degree Of Operation Ratio. From the results of this analysis can be concluded as follows : (1) The company's total sales value is greater than the value of sales at the level of the break even point. It can be shown from the comparison table between the total value of sales by value of sales at the break even point. The average sales total is Rp 2,113,954,400.00 while the average level of sales at the break even point is Rp 1,999,576,794.00. So the first hypothesis which states that the value of the company's total sales were above the level of sales at the break even point. (2) Margin Of Safety Ratio corporate average smaller than the Contribution Margin Ratio corporate average margin of safety ie the average is at 5.52 % while the Contribution Margin Ratio is average by 85.85 %. So the second hypothesis which states that the Margin of Safety Ratio under the Contribution Margin Ratio is received. (3) Degree of Operation Leverage (DOL) for the lowest company high of 14.79 and 20.25 (positive). Means the third hypothesis which states that the value of sales of a positive effect on operating income is received. Based on the conclusions that can be implied as follows : (1) In the work plan and budget necessary to complete the company's profit analysis break even point, because by using the break even point analysis can be known relationship between the magnitude of the cost, selling price, the value of sales and profits to be planned for the coming time. (2) Companies need to maintain and even increase the value of sales by expanding the area of marketing, both domestically and abroad. This meant that the difference between the value of total sales by value of sales at the level of the break even point is larger, because the difference in value greater sales of the company can avoid impairment losses in case of sale of the company to the extent of security (Margin Of Safety). It also meant that the company can maintain the selling price has been achieved. Keyword : Break Event Point, Budgeting System